The Efficacy of Intra-Articular Methylprednisolone Injections in Treating Idiopathic Frozen Shoulder: Descriptive Case Series Study - Abdul Hameed, Aman Ullah Khan Kakar, Khushal Khan, Attiq Ur Rehman, Irfan Adil, Saleem Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Frozen shoulder is a clinical condition marked by painful limitations in both active and passive shoulder movements. There are several therapeutic options available aimed at restoring mobility and alleviating pain for individuals suffering from frozen shoulder. A significant indicator of this condition is the restriction of shoulder movement in all directions, affecting both passive and active ranges of motion. Objective: To assess the effectiveness of intra-articular methylprednisolone injections in treating idiopathic frozen shoulder. Methodology: This descriptive case series study was carried out in the Department of Orthopaedics at Bolan Medical College in Quetta. The study included patients aged between 30 and 60 years, of both genders, who were diagnosed with unilateral idiopathic (primary) frozen shoulder, specifically in phases I and II, and had experienced symptoms for less than six months. Participants were required to have a University of California Los Angeles (UCLA) shoulder rating scale score of 27 or lower. A 4cc injection was administered, consisting of 1cc of methylprednisolone (equivalent to 40mg) and 3cc of 2% lignocaine. The functional outcome was deemed acceptable according to the operational definition at the conclusion of the 12th week following the injection. Results: The average age of the patients was 43.10 years, with a standard deviation of 9.66 years. A significant portion of the cohort, 59 patients (67.80%), was male, while 28 patients (32.20%) were female. The mean duration of symptoms reported was 3.58 months, with a standard deviation of 1.09 months. In most cases, 63 patients (72.40%) experienced symptoms for four months or less. A satisfactory functional outcome was noted in 52 patients, accounting for 59.80% of the total. Conclusion: A satisfactory functional result from intra articular injection of methylprednisolone was noted in 52 patients, accounting for 59.80%, who were diagnosed with idiopathic frozen shoulder. Keywords: idiopathic frozen shoulder, acceptable functional outcome, intra articular injection, methylprednisolone